Racism: Projective Identification and Cultural Processes - Young, Robert (PINS-Psychology in Society, 2026)
It is surely appropriate that since the date of this conference falls so close to the five hundredth anniversary of Columbus Day we should look at the racism of the New World. It is a sombre story, so distressing that it has attracted the attention of Ridley Scott, the director most able to plumb the dark side of human nature. The creator of "Blade Runner", an analysis of the boundaries of humanity and "Alien", the embodiment of Thanatos, now bring Gerard Depardieu to us as Columbus and promote Sigourney Weaver from Warrant Officer Ripley to Queen Isabella in his new film, "1492", appropriately subtitled "Conquest of Paradise".